2014
DOI: 10.1007/s10071-014-0781-9
|View full text |Cite
|
Sign up to set email alerts
|

Domestication effects on behavioural traits and learning performance: comparing wild cavies to guinea pigs

Abstract: The domestication process leads to a change in behavioural traits, usually towards individuals that are less attentive to changes in their environment and less aggressive. Empirical evidence for a difference in cognitive performance, however, is scarce. Recently, a functional linkage between an individual's behaviour and cognitive performance has been proposed in the framework of animal personalities via a shared risk-reward trade-off. Following this assumption, bolder and more aggressive animals (usually the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 54 publications
5
32
0
Order By: Relevance
“…Similar phenomena have been noted for a wide range of animal taxa (Wurbel et al, 2006), including Passeriformes and humans . In support of this hypothesis, two recent studies on the American mink and the Guinea pig, species intensively bred for commercial and pet purposes, have demonstrated that individuals can be selected to minimize their stereotypic and aggressive behaviours, resulting in improved health and wellbeing (Hansen et al, 2010;Brust and Guenther, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…Similar phenomena have been noted for a wide range of animal taxa (Wurbel et al, 2006), including Passeriformes and humans . In support of this hypothesis, two recent studies on the American mink and the Guinea pig, species intensively bred for commercial and pet purposes, have demonstrated that individuals can be selected to minimize their stereotypic and aggressive behaviours, resulting in improved health and wellbeing (Hansen et al, 2010;Brust and Guenther, 2014).…”
Section: Discussionmentioning
confidence: 77%
“…If performance across tasks is repeatable, we would expect positive relations between sociopositive behaviour and learning as well as between boldness and aggressiveness, as detected in our earlier paper (Brust & Guenther 2015), to be also stable over time. However, if we find performance to be instable over time, we would not expect a consistent linkage between the classical personality traits and cognition.…”
Section: Introductionmentioning
confidence: 69%
“…This procedure has proved to work well for single testing these highly social mammals in a number of previous studies (e.g. Brust & Guenther 2015;Guenther et al 2013). Stimuli were presented on a brick that was integrated into the bedding of the home cage and provided a flat surface.…”
Section: Animals and Housingmentioning
confidence: 94%
See 2 more Smart Citations